1995
DOI: 10.1128/jb.177.5.1239-1246.1995
|View full text |Cite
|
Sign up to set email alerts
|

Structure and regulation of a Candida albicans RP10 gene which encodes an immunogenic protein homologous to Saccharomyces cerevisiae ribosomal protein 10

Abstract: , Infect. Immun. 61:4263-4271, 1993). cDNA10 was used to isolate its cognate gene, and both the cDNA and gene were sequenced, revealing a major open reading frame with the potential to encode a basic protein of 256 amino acids with a predicted molecular weight of 29 kDa. Over its entire length, the open reading frame showed strong homology at both the nucleic acid (75 to 78%) and amino acid (79 to 81%) levels to two Saccharomyces cerevisiae genes encoding the 40S ribosomal protein, Rp10. Therefore, our C. albi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

1996
1996
2001
2001

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 55 publications
(55 reference statements)
0
34
0
Order By: Relevance
“…The expression of many other C. albicans genes fluctuates in response to the inducing conditions during the yeast-to-hypha transition rather than to morphogenesis itself. These genes encode proteins involved in wideranging functions such as glycolysis (ADH1, PYK1, GPM1, and PGK1 [67]), protein synthesis and folding (TEF3, RP10, and HSP90 [65,66,69]), cell wall biosynthesis (CHS1, CHS2, CHS3, and GFA1 [10,24,59]), and formation of the cytoskeleton (ACT1 [13,66]). We know of only one C. albicans mRNA (HST7) that remains at relatively constant levels during the yeast-to-hypha transition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The expression of many other C. albicans genes fluctuates in response to the inducing conditions during the yeast-to-hypha transition rather than to morphogenesis itself. These genes encode proteins involved in wideranging functions such as glycolysis (ADH1, PYK1, GPM1, and PGK1 [67]), protein synthesis and folding (TEF3, RP10, and HSP90 [65,66,69]), cell wall biosynthesis (CHS1, CHS2, CHS3, and GFA1 [10,24,59]), and formation of the cytoskeleton (ACT1 [13,66]). We know of only one C. albicans mRNA (HST7) that remains at relatively constant levels during the yeast-to-hypha transition.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we attempted to identify C. albicans genes which are regulated specifically in response to morphogenesis. Using various approaches, we identified numerous genes that are regulated during morphogenesis, including HSP90, TEF3, ADH1, PYK1, RP10, and GFA1 (59,[65][66][67]69). However, in all cases we showed that these genes were responding to changing growth conditions rather than to morphogenesis.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…After amplification (2 min at 94 mC followed by three-step cycling of 30 s denaturation at 94 mC, 15 s annealing at 57 mC, 30 s extension at 72 mC, and 2 min final extension at 72 mC) the resulting PCR fragment was cut with HindIII and SalI and ligated into the abovedescribed pMAL\EFB3hUTR\URA3 to yield pCaOSS. The sequence of the 1674 bp fragment bearing CaRP10 was amplified from C. albicans SGY-243 genomic DNA with RP10-5h\RP10-3h primers (Table 2), which were designed based on the fragment 3156 of Contig5 of the C. albicans sequencing project at Stanford University (sequencewww.stanford.edu\group\candida), and was obtained by using the GenBank X82017 entry (Swoboda et al, 1995) as a query against the C. albicans database. PCR conditions were : initial denaturation for 3 min at 94 mC, followed by three-step cycling of 30 s denaturation at 94 mC, 30 s annealing at 57 mC, 1 min 30 s extension at 72 mC, for 30 cycles, and 7 min final extension at 72 mC.…”
Section: Methodsmentioning
confidence: 99%
“…The final plasmid construction step was amplification and cloning of a target region into the vectors carrying the above-described genes to ensure stable integration into the genome of the recipient C. albicans SGY-243 cells following transformation. The CaRP10 locus was chosen to serve this purpose (Swoboda et al, 1995 ;Care et al, 1999 ;Backen et al, 2000). We chose SGY-243 as the recipient strain since it has a very similar profile of histatin sensitivity as the clinical isolate (DS1) we have previously studied (Edgerton et al, 1998).…”
Section: Construction Of C Albicans Strains Bearing Genetically Engimentioning
confidence: 99%